2016
DOI: 10.1074/jbc.m116.739326
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Novel Nuclear Factor of Activated T Cell (NFAT)-associated Proteins in T Cells

Abstract: Transcription factors of the nuclear factor of activated T cell (NFAT) family are essential for antigen-specific T cell activation and differentiation. Their cooperative DNA binding with other transcription factors, such as AP1 proteins (FOS, JUN, and JUNB), FOXP3, IRFs, and EGR1, dictates the gene regulatory action of NFATs. To identify as yet unknown interaction partners of NFAT, we purified biotin-tagged NFATc1/αA, NFATc1/βC, and NFATc2/C protein complexes and analyzed their components by stable isotope lab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
40
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 96 publications
0
40
0
Order By: Relevance
“…NFAT is a transcription factor that is predominantly regulated by activation and the subsequent translocation from the cytoplasm to the nucleus. NFAT activation/regulation is measured by total NFAT2 protein/mRNA expression levels (45,46). The results demonstrated that the ARB VAL attenuated the HG-induced increase of TRPC6 and NFAT in podocytes in vivo and in vitro.…”
Section: Discussionmentioning
confidence: 94%
“…NFAT is a transcription factor that is predominantly regulated by activation and the subsequent translocation from the cytoplasm to the nucleus. NFAT activation/regulation is measured by total NFAT2 protein/mRNA expression levels (45,46). The results demonstrated that the ARB VAL attenuated the HG-induced increase of TRPC6 and NFAT in podocytes in vivo and in vitro.…”
Section: Discussionmentioning
confidence: 94%
“…In addition, NFAT is an important nuclear transcription factor of T cell activation that is also regulated by miRNAs. 31,32 In the present study, we found that PAMK treatment signicantly increased the expression of NFAT in the presence of CTX, but not NF-kB, indicating that PAMK might upregulate the expression of novel_mir2 to inhibit CTLA4, leading to increased levels of nuclear transcription factor NFAT, which ultimately changes the expression of cytokines and promotes T cell activation. This means that the mechanism by which PAMK promotes T cell activation, inhibited by CTX in geese, is not the same as the mechanism by which CMP promotes macrophage activation.…”
Section: Discussionmentioning
confidence: 75%
“…Pathway analyses showed that TNF signaling and downstream pathways such as IL-1B and NF-κB were more active in CD8 + T cells of resistant RMs, as were pathways initiated by TcR ligation such as CAVI and HIF-1α. CREB1, a transcription factor that binds to NFATc1 and 2 in activated T cells ( Gabriel et al, 2016 ) and RE1 Silencing Transcription Factor (REST), which reduces the activity of NFATs ( Ohba et al, 2006 )(Supplementary Table S5).…”
Section: Resultsmentioning
confidence: 99%